Liquid-liquid domain miscibility driven by composition and domain thickness mismatch in ternary lipid monolayers - Fanani, Maria Laura (2010)
This work describes how changes in surface pressure modulate the molecular organization of Langmuir monolayers formed by ternary mixtures of dlPC/pSM/Dchol that exhibit coexistence of liquid-expanded (LE) and liquid-ordered (Lo) phases. It provides a theoretical framework for understanding the pressure-induced critical miscibility point characteristic of monolayer systems with liquid-liquid phase coexistence. From compression isotherms and Brewster Angle Microscopy of Langmuir monolayers with a composition close to a tie line, we determined experimental values of mean molecular areas, surface potential, monolayer thickness, and could estimate the mean molecular area and composition of each coexisting phase. A surface pressure-induced enrichment of the PC component in the Lo phase reduces both the compositional miscibility gap and the hydrophobic mismatch between phases. The liquid-liquid miscibility transition point observed at ¡Ö25mN/m can be explained by a competition between thermal energy and the line tension arising from the hydrophobic mismatch between the coexisting liquid phases.